Macrocyclic Lanthanide(III) Complexes with a 14-Membered Tetraaza Ambivalent Ligand - RAI, H.C.; CHAKRABORTI, I.; KUMAR, ASHWINI (Asian Journal of Chemistry, 2010)
A series of complexes of the type [Ln(mac)CI2(H2O)2]Cl Ln = La, Pr, Nd, Sm, Eu, Gd, Th and Dy; mac = 1,4,8,11-tetraazacyclotetradeca- 2,3-dione] have been prepared by template reaction of the lanthanide ion. The ligand has been obtained by the reaction of 1, 10-diamino-4, 7 -diazadecane with diethyloxalate. The complex [La(mac)CI2(H2O)2]CI reacts with lanthanide chlorides to yield the complexes of the type [ La(mac)CI2(H2O)2 LnCI3(H2O)2]CI. The chemical composition of both the mononuclear and trinuclear complexes have been established from analytical, molar conductance and FAB mass data It is observed that the macrocycle is bonded in a tetrakis manner in the mononuclear complexes and in a hexakis manner in the trinuclear complexes. The coordination number eight around the encapsulated metal ions and nine around the exocyclic oxygen bonded metal ion are established from infrared and electronic spectral studies. The symmetry of the ligand field around the metal ion is indicated from the emission spectra.